Economics of Depletable Resources: Market Forces and Intertemporal Bias - Sweeney, James L. (Review of Economic Studies, 1977)
Journal Article Economics of Depletable Resources: Market Forces and Intertemporal Bias Get access James L. Sweeney James L. Sweeney Federal Energy Administration and Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 125–141, https://doi.org/10.2307/2296977 Published: 01 February 1977 Article history Received: 01 August 1974 Accepted: 01 February 1976 Published: 01 February 1977